Impact of organisational culture, social influence and facilitating conditions on whatsapp's official usage among university academicians in Malaysia - Mohsin Ali, Rana (2019)
The advancements in communication technology have changed the way and pattern with which people communicate and disseminate information. Especially the integration of mobile communication technologies and social media in people’s daily lives, have impacted the traditional way of communication. Among these technologies, social media and social networks carry significant place for communication and sharing of knowledge within the organisation. New social media, such as WhatsApp, have seen dramatic growth with reports suggesting an increase of up to 1 million users per day, reaching some 1 billion users with a daily engagement higher than the industry standard. Despite of high usage of WhatsApp within organisations, a little is known whether these channels are formal or informal and information passed through these channels is legitimate or otherwise. Since many factors affect the adoption/usage of these new technologies within organisations, culture is one of the most important factor for this reason as recognised by researchers. Also organisational culture is the main factor to adopt a formal or informal channel of communication. So this study sees the impact of organisational culture (involvement, consistency, adaptability and mission), social influence, and facilitating conditions on WhatsApp’s official usage by Malaysian academicians with the help of technology acceptance model (perceived usefulness, perceived ease of use, WhatsApp’s official usage). In a sample of 328 academicians, the results of the study state that consistency, adaptability, social influence and facilitating conditions show significant impact on perceived usefulness, however mission and involvement did not show significant relationship with perceived usefulness. On the other hand, that involvement, consistency, mission and social influence show significant relationship with perceived ease of use, however adaptability and facilitating conditions did not show any significant relationship with perceived ease of use. The study also confirms that antecedents of TAM (perceived ease of use and perceived usefulness) mediate the relationship between endogenous and exogenous variables of this study. These findings confirm the relationship between organisational culture social influence and WhatsApp’s official usage in Malaysian universities. However facilitating conditions does not show strong relationship with the whatsapp’s official usage. These findings have implications for research and practice. These implications, as well as the limitations and recommendations for future research of the study, are discussed.